2004
DOI: 10.1016/j.jaci.2004.07.052
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of fluticasone propionate and salmeterol on in vitro T-cell activation and apoptosis in asthma

Abstract: Background: In asthma T cells are characterized by an increased activation state and by reduced apoptosis. Objective: Because the clinical efficacy of inhaled corticosteroids combined with long-acting b 2 -agonists has been widely demonstrated in asthma, we studied, in vitro, the effect of fluticasone propionate (FP) and salmeterol alone and in combination on the activation and apoptosis of peripheral blood T cells (PBTs), on the expression of phosphorylated nuclear factor kB inhibitor (IkBa), and on the nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
2
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 31 publications
5
32
2
3
Order By: Relevance
“…However, in vitro studies have suggested that there are dose-dependent effects of fluticasone on the inhibition of IL-8 and other mediators released from various types of cells, including airway epithelial cells [24], smooth muscle cells [25] and fibroblasts [26]. A synergistic effect of SFP on the inhibition of mediator release has also been demonstrated [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…However, in vitro studies have suggested that there are dose-dependent effects of fluticasone on the inhibition of IL-8 and other mediators released from various types of cells, including airway epithelial cells [24], smooth muscle cells [25] and fibroblasts [26]. A synergistic effect of SFP on the inhibition of mediator release has also been demonstrated [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore we did not observe any alteration in bone density and biochemical markers of bone turnover, since another concern is the reduction of bone density that may result from use of high doses of ICS for long-term therapy (17). BMD is usually measured by DEXA since this method is extremely In theframe patients selectedfor the prospective study (n. [9][10][11][12][13][14][15][16][17][18][19]; I Calcium. Phosphorus and Alkaline phosphatase were determined in blood; 2 Calcium clearance was calculated using thefollowingformula: urine calcium/urine creatinine.…”
Section: 'mentioning
confidence: 99%
“…Specific and standardized diagnostic tests for children are not yet available and chronic disease itself might affect growth and bone mineral density (BMD) (13). Moreover, several reports suggest that FP can influence T-cell activation and function ( 14).…”
mentioning
confidence: 99%
“…Furthermore, fluticasone propionate was shown to control peripheral blood T-cell activation and induce T-cell apoptosis through activation of caspases 8 and 3 in mild-persistent asthmatics [61]. VIGNOLA et al [62] showed that in mild-persistent asthmatics, low-dose fluticasone propionate was effective in improving symptoms due, at least in part, to the resolution of eosinophilic bronchial inflammation and downregulation of remodelling markers, such as MMP-9 and TIMP-1 levels in induced sputum samples.…”
Section: Foxp3mentioning
confidence: 99%